Analisis Tren Pembiayaan Alternatif Digital: Studi Kasus Paylater Kredivo di Indonesia - Muhammad Nara Rafli Prasetyo; Handy Nugraha (JURNAL ILMIAH EDUNOMIKA, 2026)
The use of paylater services in Indonesia continues to rise, particularly for online shopping. However, this growth also increases the risk of default and consumer debt. Therefore, it is important for the public to understand the factors that influence the use of paylater services. This study aims to analyze the influence of the Provincial Minimum Wage, Gross Regional Domestic Product, and Information and Communication Technology skills on the percentage of Kredivo Paylater users in Indonesia. Based on a literature review conducted by the researchers, this study is the first to directly link ICT skills with the use of Kredivo Paylater in Indonesia. This study employs a quantitative approach using panel data regression analysis across 10 provinces for the period 2021–2023. The results indicate that ICT skills significantly influence the use of Kredivo Paylater. As the public’s ICT skills improve, this will drive the development of the paylater industry, thereby increasing the likelihood of achieving financial inclusion and enhancing public welfare. These findings are expected to serve as a reference for research on the digital economy particularly in the fintech paylater sector as well as a basis for policy considerations regarding the digital economy in Indonesia.